Pengaruh rasio keuangan terhadap financial distress di masa pandemi covid-19 - Oktaviani, Fefianti Dwi Putri; Yanthi, Merlyana Dwinda (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of writing in this article is to find out how profitability, liquidity and leverage affect financial difficulties. The population, in 2020 there are 78 F&G and transportation companies in the 2020 IDX. This is a type of qualitative research with secondary data from company finance reports. This study tries to use a purposive sampling technique which has a total sample of 67 from 78 companies. SPSS version 23 application was used for data analysis of the form of logistic regression. This study resulted in <0.05 which is a significant value. This shows that profitability, liquidity and leverage influence each other to predict companies in financial distress. Partially, according to the test results based on the model test, the profitability and leverage variables have a significance value > 0.05, and also these variables do not affect financial distress conditions. While the liquidity variable has a significance value of <0.05, so liquidity has a negative effect on financial distress conditions.